Non-linear regressio analysis for unconstrained optimization using numerical differentiation - Romero Silva, Rafael (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
Regression analysis is a method for establishing t he flffictional relationship between two variables where the variation in one measurement is considered while the other 15 held fixed. In many engineering situations a straight-line relationship can express the dependence of one variable on another. This is referred to as the linear regression analysis. The relationship is Y=.~ + A1 X fir 5t-order equation where Y = dependent variable,which is measured at a given l evel of X X= independent variable, which i5 held fixed; Ao,A, = regression parameters to be determined from sample data.